Infections of heart stimulating systems and implantable cardioverters-defibrillators. A problem for cardiologists and cardiac surgeons - Bartczak, Karol; Walczak, Andrzej; Jander, Sławomir; Bitner, Mirosław; Kośmider, Anna; Banyś, Andrzej; Maciejewski, Marek; Piestrzeniewicz, Katarzyna; Piechowiak, Monika; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
This paper presents the issue of infective endocarditis related to the infection of the implanted heart stimulating system (pacemaker) or implantable cardioverters-defibrillators. Having long-lasting experience in both implanting and extracting heart stimulating systems, the authors try to find a patient-safe consensus on management of such cases, basing on a history of a 33-year-old patient.